2012
DOI: 10.2174/1874325001206010482
|View full text |Cite
|
Sign up to set email alerts
|

Intramedullary Fixation of Diaphyseal Clavicle Fractures Using the Rockwood Clavicle Pin: Review of 86 Cases

Abstract: Aim:This study reports the safety, efficacy and functional and patient centred outcomes of the largest published series of patients treated with the Rockwood clavicle pin (intramedullary device) to date.Patients and Methods:A retrospective review of case notes, radiographs and follow-up by questionnaire was conducted. 86 patients were operated upon, 70 for acute fractures (group A) and 16 for non-union (group B). Results: Rate of non-union was 2 (2.9%) in group A and 0 in group B. Mean Disability of the Arm, S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
17
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(18 citation statements)
references
References 31 publications
(34 reference statements)
1
17
0
Order By: Relevance
“…1). In total, 10 studies concerning the Rockwood (DePuy, Warsaw, IN, USA) and Hagie pin (Smith & Nephew, Memphis, TN, USA) were identified and included in the analysis (two level I, [15,16] two level III [17,18] and six level IV [19][20][21][22][23][24] studies). These devices were evaluated together since they are essentially the same; they both consist of the exact same stainless-steel pin, with a cancellous and machine thread end, and two nuts.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…1). In total, 10 studies concerning the Rockwood (DePuy, Warsaw, IN, USA) and Hagie pin (Smith & Nephew, Memphis, TN, USA) were identified and included in the analysis (two level I, [15,16] two level III [17,18] and six level IV [19][20][21][22][23][24] studies). These devices were evaluated together since they are essentially the same; they both consist of the exact same stainless-steel pin, with a cancellous and machine thread end, and two nuts.…”
Section: Resultsmentioning
confidence: 99%
“…This may be explained by the two bulky nuts at the posterolateral aspect of the clavicle where the pin is inserted and is has been reported to be an important disadvantage of the implant. [15,19,22] For the Sonoma CRx no reports on hardware irritation were found since this device has no extra-cortical prominences and is fully embedded in the clavicular cortex.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…5 Wijdicks et al suggested that infection is defined as redness, swelling, purulent discharge, a positive wound culture, and/or when prescription of antibiotics was given, and irritation was caused by prominence or protrusion of the implant material. 6 There are only few articles [7][8][9][10][11][12][13] reporting on these complications and even fewer 14,15 explore their treatments and outcomes, especially with IM cannulated screws. 16,17 Our study was designed to focus on the treatment and outcome of patients with clavicle fractures treated with open reduction and internal fixation, who had local wound complications.…”
Section: Introductionmentioning
confidence: 99%
“…Through a retrograde intramedullary nailing of the screw, a technique introduced by Boehme et al, 12) many authors have shown good clinical outcomes. [13][14][15][16] We devised an anterograde intramedullary nailing approach to treat clavicle shaft fractures and used that along with the previously described retrograde approach. The purpose of this study was to investigate and compare the outcomes of retrograde intramedullary screw fixation and of anterograde intramedullary screw fixation for clavicle shaft fractures.…”
Section: Introductionmentioning
confidence: 99%